Penerapan Konsep Value Engineering pada Proyek Bangunan Gedung Sekolah : (Studi Kasus: Madrasah Ibtidaiyah Negeri 3 Gunungsitoli) - Ryobi Irfanto; Iwan Saputra N W; Hans Dermawan (Jurnal Teknik Sipil, 2023)
The cost aspects of construction projects are very diverse, such as overbudget, overtime, etc. which are grouped as unnecessary costs. The concept of value engineering can optimize the unnecessary costs. Value engineering is a technique for analyzing job functions or processes to determine "best value", or the best relationship between value and cost. This study aims to apply value engineering to a school building project with a case study of Madrasah Ibtidaiyah Negeri 3 Gunungsitoli. Value engineering consist of the preparation stage, the function analysis stage, the creative stage, the evaluation stage, and the recommendation stage. The preparation stage uses the Pareto principle to find out the work of great value to be carried out. The function analysis stage is used to sort out the main and supporting materials, and calculate the cost/worth of the work. The creative stage is finding alternative materials that can replace without changing the function. The evaluation stage is carried out to calculate the latest value of each alternative material. Finally, the recommendation stage is to recommend alternative materials with the lowest costs. The need of data is the Budget Plan (RAB), Unit Price Analysis (AHS), and material data from planners who apply the value engineering. The result of budget planed efficiency is IDR244.531.582 which is 3.76% lower than total initial project’s budget.